Respostas
respondido por:
0
A(3,2) e B(-2,-1)
M = ( yb - ya ) / ( xb - xa ) = ( -1 - 3 ) / ( -2 - 2 ) = -4/-4 = 4/4 = 1
y - ya = m ( x - xa )
y - 2 = 1 ( x - 3 )
y - 2 = x - 3
y = x - 3 + 2
x - y - 1 = 0 ( equação geral )
y = x - 1 ( equação reduzida )
M = ( yb - ya ) / ( xb - xa ) = ( -1 - 3 ) / ( -2 - 2 ) = -4/-4 = 4/4 = 1
y - ya = m ( x - xa )
y - 2 = 1 ( x - 3 )
y - 2 = x - 3
y = x - 3 + 2
x - y - 1 = 0 ( equação geral )
y = x - 1 ( equação reduzida )
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás